2013
DOI: 10.1186/1687-6180-2013-105
|View full text |Cite
|
Sign up to set email alerts
|

Coherent CFAR detection in compound Gaussian clutter with inverse gamma texture

Abstract: Recent publications have explored coherent radar detection in a compound Gaussian clutter environment with inverse gamma texture, since the latter clutter model has been validated for X-band high-resolution maritime surveillance radar clutter returns. This paper explores the development of coherent constant false alarm rate (CFAR) detectors for this scenario. In the first instance, a detector is constructed with explicit knowledge of the clutter parameters. It is then shown that the probability of false alarm/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Coherent detection schemes, based upon a Pareto intensity model, have been analysed in several recent papers [9,[12][13][14][15]. From the incoherent perspective, [16] analyses classical integrators.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Coherent detection schemes, based upon a Pareto intensity model, have been analysed in several recent papers [9,[12][13][14][15]. From the incoherent perspective, [16] analyses classical integrators.…”
Section: Background and Motivationmentioning
confidence: 99%
“…If most of the target energy is concentrated in one range cell, the performance of the three detectors is degraded. From (16), (20), and (27), the detection statistics of the three detectors are expressed as the product or logarithmic sum of the returns in the J range cells. Therefore, if the total target energy in all the J range cells is given, it can be concluded that the detection statistics achieve their maximum value when the target energy is uniformly distributed.…”
Section: Performance Assessmentmentioning
confidence: 99%
“…Some heavy-tailed radar clutter models, such as K distribution [16][17][18], Pareto distribution [19,20], KK distribution [21,22], are utilized in the target detection scheme design. In [16], the K-distribution is expressed as spherically invariant random process and then two CFAR detectors, i.e., scatterer density dependent GLRT (SDD-GLRT) and non-scatterer density dependent GLRT (NSDD-GLRT), are proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress has been reported in [12][13][14], which examine the problems associated with coherent detection. Owing to difficulties with covariance matrix estimation, incoherent detection schemes have also been examined [15,16].…”
Section: Introductionmentioning
confidence: 98%